Isolated ballistic non-abelian interface channel - Dutta, Bivas; Umansky, Vladimir; Banerjee, Mitali; Heiblum, Moty (Science (American Association for the Advancement of Science), 2022)
The topological order of a quantum Hall state is mirrored by the gapless edge modes owing to bulk-edge correspondence. The state at the filling of ν = 5/2, predicted to host non-abelian anyons, supports a variety of edge modes (integer, fractional, neutral). To ensure thermal equilibration between the edge modes and thus accurately determine the state’s nature, it is advantageous to isolate the fractional channel (1/2 and neutral modes). In this study, we gapped out the integer modes by interfacing the ν = 5/2 state with integer states ν = 2 and ν = 3 and measured the thermal conductance of the isolated-interface channel. Our measured half-quantized thermal conductance confirms the non-abelian nature of the ν = 5/2 state and its particle-hole Pfaffian topological order. Such an isolated channel may be more amenable to braiding experiments. The nature of some fractional quantum Hall (FQH) states can be determined by measuring the thermal conductance of the state’s edge. Such measurements have suggested that the well-known FQH state at 5/2 filling, which is thought to harbor non-Abelian quasiparticles, features the so-called particle-hole Pfaffian topological order. However, the possibility that the edge modes were not thermally equilibrated left room for alternative interpretations. To avoid this ambiguity, Dutta et al . created an isolated edge consisting only of a 1/2 charge mode and a neutral edge mode by interfacing the fractional 5/2 state with integer quantum Hall states. The measurement of the thermal conductance of this isolated state reaffirmed the particle-hole Pfaffian character of the 5/2 state. —JS Thermal conductance of an isolated fractional quantum Hall edge state at 5/2 filling reveals its topological order.